2014
DOI: 10.1002/hed.23680
|View full text |Cite
|
Sign up to set email alerts
|

Somatic mutations in the D‐loop of mitochondrial DNA in head and neck squamous cell carcinoma

Abstract: Somatic mutation of D-loop of mtDNA was a potential prognostic factor of head and neck squamous cell carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Recently, two groups [ 17 , 18 ] reported that most of missense mutations of mtDNA do not have distinct physiological advantages, indicating that these mutations are not under positive selection. In addition, several studies also concluded that mtDNA mutations are not related to the developments of most cases of lung cancer [ 19 ] and head and neck squamous cell carcinoma [ 20 ]. All of these lines of evidence seem to be contradictory to the critical roles of mtDNA mutations in tumor development, leaving unclear whether somatic mtDNA mutations are drivers, or just bystanders, of tumor development.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, two groups [ 17 , 18 ] reported that most of missense mutations of mtDNA do not have distinct physiological advantages, indicating that these mutations are not under positive selection. In addition, several studies also concluded that mtDNA mutations are not related to the developments of most cases of lung cancer [ 19 ] and head and neck squamous cell carcinoma [ 20 ]. All of these lines of evidence seem to be contradictory to the critical roles of mtDNA mutations in tumor development, leaving unclear whether somatic mtDNA mutations are drivers, or just bystanders, of tumor development.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the incidence rates of head and neck cancer have risen in many countries over the past decade 2 . Although better combinations of loco-regional plus systemic therapeutic modalities have improved the quality of life after treatment, the 5-year survival rate has not changed much in recent years 3 4 .…”
mentioning
confidence: 99%
“…One more interesting observation is that chewers (24 %, i.e., n=14) are more susceptible to mtDNA mutation compared to smokers (10 %, i.e., n=3) ( Table 4). This might be due to oxidative DNA damage inflicted by generation of more ROS in oral cavity of chewers who used tobacco, areca nuts and lime, and same has been observed in other studies [41,42] although recent data suggests that most of the mtDNA mutations in tumor arose during replication of mtDNA [35]. Previously, most of the reports have done crude estimates to compare the incidence of mutations among patients and controls.…”
Section: Discussionmentioning
confidence: 74%
“…Mutations in mtDNA have been reported in different cancers and most of such mutations accumulate in D-loop which is a control region of mitochondria replication and transcription [10,14,22,41,42]. Over the years, several studies have reported mutations in D-loop of different cancers though mutation rates have been highly variable: 21, 29, and 62 % of samples were reported to harbor D-loop mutations in head and neck cancer [9,12,16], 35 % of samples were found to harbor D-loop mutations in gastric cancer [22] whereas in cervical cancer, 95 % of the samples were reported to have mutated D-loop [14].…”
Section: Discussionmentioning
confidence: 99%